Rwanda and Ethiopia: Developmental Authoritarianism and the New Politics of African Strong Men. (1st September 2015) - Matfess, Hilary
Abstract: Current classification systems create typologies of authoritarian regimes that may overlook the importance of national policies. Rwanda and Ethiopia in particular are perplexing case studies of post-1990s governance. Both nations are characterized by high growth economies with significant state involvement and the formal institutions of democracy, but deeply troubling patterns of domestic governance. This article proposes a new category of authoritarianism called "developmental authoritarianism, " which refers to nominally democratic governments that provide significant public works and services while exerting control over nearly every facet of society. The article then reflects upon the durability and implications of this form of governance.